A case study on how to address difficulty in donning and doffing of clothing for a child with motor impairments - Albarracin, Marina Myrtel H.
Inclusivity in the fashion industry is of utmost importance especially for People with Disabilities (PWDs). Addressing the clothing-related needs of this group of individuals will help improve their quality of life, and increase the rate of holistic development, especially among children. This study aimed to develop clothing that could alleviate the difficulty of donning and doffing garments for a selected Filipino child with motor impairments and/or disabilities. The participant, a 10-year-old male, diagnosed with Level V Spastic Cerebral Palsy, was selected using non-probability, convenience sampling. The study was divided into two phases. Phase 1 focused on needs identification and Phase 2 focused on prototype sample development. Both phases made use of interviews and observations done online as the primary data gathering tools. All data was organized into a data collating sheet and analyzed to be able to be applied into the design and construction of a prototype t-shirt sample. It was observed that the main concern of participant was his inability to control his stiffened limbs, which makes it difficult to don and doff top garments. To address this, the fit on the armholes need to be looser, the fabric to be used should have increased amount of stretch, and an accessory that can make the opening and closing of the placket easier should be used. In designing the prototype sample, the armhole pattern was adjusted to be wider, a cotton-spandex blended knit fabric was used, and magnetic fasteners in the plackets placed along the side seams were added. The fit test showed that the prototype sample made the donning and doffing of the garment on the participant a lot easier. The researcher recommends further studies in this scope of knowledge to encourage more companies catering to inclusive clothing for PWDs and to do more studies using a larger population size to be able to identify all the common needs found within this group of individuals.